Analisis Data Penjualan Handphone Poco F4 di Tahun 2022 - M. Rizki Mahrifan (PT. ZIVANA CENDEKIAWAN BANGSA, 2025)
Handphone Poco F4 sales in 2022 have been a major focus in this study to understand the factors influencing consumer preferences in the technology market. This topic was chosen because of its significant relevance in the context of community service, which is to provide insights to manufacturers regarding consumer preferences for more effective product development. The research method involves analyzing sales data, consumer surveys, and literature reviews to identify factors key that affects the purchase of the HP Poco F4. The results show that competitive pricing, superior technical specifications, and effective marketing strategies contribute significantly to the increase in sales of these products. Overall, HP Poco F4 sales have experienced consistent growth across various global markets, demonstrating the importance of understanding and responding appropriately to consumer needs. The study provides valuable guidance for the industry in developing products and marketing strategies that are relevant to the ever-evolving market.